PERANAN KOMUNIKASI INTERNAL PIMPINAN DALAM MENINGKATKAN KINERJA KARYAWAN DI HOTEL ASHYANA CANDIDASA BEACH RESORT KARANGASEM, BALI - I Ketut Murdana (Pusat penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2022)
The research aimed at studying and analyzing the roles of internal management communication in order to increase the staff performances at Ashyana Candidasa Hotel Beach Resort, Karangasem, Bali. The primary research data are directly collected from the management of Ashyana Beach Resort Hotel as a key informan during the structured interview processes and also from the research questionnaires compilation. The informan were using abundant sampling techniques with the total numbers of 25 samples are analysed. The research revealed that 6,25% answered the 13 questions by “YES” which meant that the internal communication has run well meanwhile 5 questions were answered by “YES/NOT” or about 5,25% which meant that internal communication has not yet run well.